The amount of citrullinated proteins in synovial tissue is related to serum anti-cyclic citrullinated peptide (anti-CCP) antibody levels. Issue 1 (January 2016) - Olivares-Martínez, Elizabeth; Hernández-Ramírez, Diego; Núñez-Álvarez, Carlos; Cabral, Antonio; Llorente, Luis
Abstract The objective of this study was to determine the relationship between citrullinated proteins in synovial tissue with peripheral anti-citrullinated peptides autoantibodies (ACPA) and peptidylarginine deiminase (PADI )PADI2, PADI3, andPADI4 messenger RNA (mRNA) expressions in synovial tissue and fibroblast-like synoviocytes in rheumatoid arthritis (RA) patients. Eleven RA and 12 osteoarthritis (OA) patients who underwent knee replacement surgery were studied. We detected citrullinated proteins in synovial tissue homogenates by western blot and serum ACPA by ELISA to anti-cyclic citrullinated peptide (anti-CCP) antibodies, andPADI2, PADI3, andPADI4 mRNA expressions in synovial tissue and in fibroblast-like synoviocytes. Patients with high amount of citrullinated proteins in synovial tissue (3 out of 7) have high levels of anti-CCP in serum. However, in the remaining 4 patients, the amount of synovial citrullinated proteins was minimal and their sera showed low levels of anti-CCP antibodies. Furthermore, we observed an increase inPADI2 mRNA expression in RA synovial tissue compared with OA patients (p  = 0.02). We detectedPADI3 mRNA in the synovial tissue of RA patients, but not in the tissue of OA patients. Even though fibroblast-type synoviocytes in RA are not the main source of PADs in the synovial tissue, they expressPADI2 mRNA moderately, PADI4 mRNA weakly, while there is no detectable expression ofPADI3 mRNA. In conclusion, we found a variety of citrullinated proteins in the synovial tissue of RA patients and the amount of such proteins is related to serum concentration of anti-CCP antibodies. We identified the presence of PADI3 mRNA expression in synovial tissue andPADI2 andPADI4 mRNA expressions in fibroblast-like synoviocytes from patients with RA.